IL-19 and Other IL-20 Family Member Cytokines in Vascular Inflammatory Diseases - Autieri, Michael V. (Frontiers in Immunology, 2018)
Cardiovascular disease remains a major medical and socioeconomic burden in developed and developing countries, and will increase with an aging and increasingly sedentary society. Many vascular diseases, and atherosclerotic vascular disease in particular, are essentially inflammatory disorders, involving multiple cell types. Communication between these cells is initiated and sustained by a complex network of cytokines and their receptors. The IL-20 family members, IL-19, IL-20, IL-22 and IL-24 initiate, sustain, and drive progression of vascular disease. are important in vascular disease as they facilitate bi-directional cross-talk between resident vascular cells with immune cells. These cytokines are grouped into the same family based on shared common receptor subunits and signaling pathways. This communication is varied and can result in exacerbation, attenuation, and even repair of the vasculature. We will briefly review what is known about IL-20, IL-22, and IL-24 in cardiovascular biology. Because IL-19 is the most studied member of this family in terms of its role in vascular pathophysiological processes, the major emphasis of this review will focus on expression and atheroprotective roles of IL-19 in vascular inflammatory disease.